Penerapan Standar Pelayanan Sesuai Undang-Undang Nomor 25 Tahun 2009 Tentang Pelayanan Publik - Muhammad Azhar Lawiya; Salmon Eliaser Marthen Nirahua; Julista Mustamu (Program Studi Hukum Diluar Kampus Utama Universitas Pattimura Kabupaten Maluku Barat Daya, 2023)
The Maluku Provincial Government as a service provider has the obligation to develop and set service standards to help the community know what kind of service will be provided. For this reason, the Maluku Provincial Government must set service standards as a benchmark in providing services. Purposes of the Research: To find out to what extent the implementation of service standards in the Maluku Provincial Government. Methods of the Research: This study uses a normative research method with the legal materials used in the research are primary, secondary and tertiary with the use of literature study techniques in the form of legal regulations, scientific works and literature. Results of the Research: he implementation of public services is an effort by the state to fulfill the basic needs and civil rights of every citizen for goods, services, and administrative services provided by public service providers. In carrying out service delivery, service standards are needed to be benchmarks, so that in carrying out public services the Maluku Provincial Government has benchmarks that can be used as guidelines for service delivery and has a reference for assessing service quality as an obligation and promise of the organizers to the community in the context of quality services. , fast, easy, affordable, and organized. However, in the implementation of public services in the Maluku Provincial Government, service standards have not been fully implemented properly, this can cause harm to the community because of the lack of transparency in the public service process carried out by the Maluku Provincial Government. For this reason, the Maluku Provincial Government is required to create and implement service standards as a benchmark in carrying out public services and as an effort to prevent maladministration in the service delivery process.